2019
DOI: 10.1016/j.omtm.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Novel Chimeric Gene Therapy Vectors Based on Adeno-Associated Virus and Four Different Mammalian Bocaviruses

Abstract: Parvoviruses are highly attractive templates for the engineering of safe, efficient, and specific gene therapy vectors, as best exemplified by adeno-associated virus (AAV). Another candidate that currently garners increasing attention is human bocavirus 1 (HBoV1). Notably, HBoV1 capsids can cross-package recombinant (r)AAV2 genomes, yielding rAAV2/HBoV1 chimeras that specifically transduce polarized human airway epithelia (pHAEs). Here, we largely expanded the repertoire of rAAV/BoV chimeras, by assembling pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 101 publications
2
46
0
Order By: Relevance
“…The development of Parvovirinae members as biologics is primarily focused on the engineering of capsids of members that can be used as viral vectors in gene delivery applications, such as the AAVs [121], or more recently also bocaviral vectors [122]. For such vectors, a transgene expression cassette is packaged into the capsids instead of the wt viral genome [123].…”
Section: Parvovirinaementioning
confidence: 99%
“…The development of Parvovirinae members as biologics is primarily focused on the engineering of capsids of members that can be used as viral vectors in gene delivery applications, such as the AAVs [121], or more recently also bocaviral vectors [122]. For such vectors, a transgene expression cassette is packaged into the capsids instead of the wt viral genome [123].…”
Section: Parvovirinaementioning
confidence: 99%
“…They combined a distinct set of AdV and bocavirus helper genes and found that rAAV titers were significantly increased when compared to rAAV vector titers that have been produced with either AdV or bocavirus helper factors alone. Lastly, other bocaviruses, such as HBoV2–4 and the gorilla bocavirus, were recently found to provide helper factors for the generation of AAV gene therapy vectors (GBoV) [ 227 ].…”
Section: Helper Viruses and Aavmentioning
confidence: 99%
“…An alternative strategy that is being investigated to deliver large genes is to leverage the capsid of the human bocavirus 1 (HBoV1), 46,47 an autonomous parvovirus relative of AAV, with a 5.5 kb genome. Indeed, it has been shown that an oversize AAV2 vector genome, including the CFTR expression cassette, can be effectively packaged in the HBoV1 capsid, resulting in efficient transduction of the human-polarized airway epithelia.…”
Section: Fitting Large Genes In a Single Aav Vectormentioning
confidence: 99%